Recognizing and Prioritizing Economic Criteria Affecting Ticket Sales Management in World Sport Mega Events - Leila Zakizadeh; Nahid Atghia; Ali Nazarian (Research in Sport Management and Marketing)
Purpose: The aim of this study was to identify and prioritize economic indicators affecting ticket sales management in important sporting events of the world.Method: According to its goal, this research was applied, and it was based on a mixed (qualitative-quantitative) method. The statistical population of the qualitative part included all countries around the world, among which the United States, Australia, China, South Korea, United Kingdom, Finland, Canada, Qatar, Germany, Turkey and Iran were selected as the statistical sample. The sample of quantitative part consisted of 12 members of Iranian sports marketing elite. In this research, various internet sites, databases, books and articles, as well as taking notes and recording documentary observations have been used. Also, in the quantitative part, first a questionnaire was designed for pairwise comparison of indicators and distributed among 12 sports marketing elites to be analyzed through hierarchical analysis.Results: The results showed that the smart and multi-purpose ticket index and ticket counter index with a weight of 0.138 and 0.020 were in the first and last rank, respectively. The results of qualitative part showed what indicators have been used to manage, prepare and distribute tickets and earn economic income in selected countries of the world.Conclusion: According to the findings, it can be stated that each of these factors has brought about results and achievements such as preventing the black market, ticket sales, event control and security, revenue generation as well as other benefits.